Unanswered Questions Surrounding the Patient Self–Determination Act - Shapiro, Robyn (Cambridge quarterly of healthcare ethics, 1992)
The Patient Self-Determination Act (PSDA) imposes new requirements on health care providers for informing patients of their rights to make decisions concerning their medical care. The Act is intended to, and is likely to, encourage patients and residents of certain healhtcare facilities to consider their treatment preferences in advance of incapacity and, in particular, to determine the circumstances in which life-sustaining treatment will be provided to them. However, many questions concerning how healthcare providers will implement the Act remain unanswered.